High concentrations of pathogenic Salmonella spp. during the wet season on bathing beaches in Makassar City, Indonesia. (April 2019) - Massinai, A; Tahir, A; Abu, N
Abstract: Pathogenic bacteria in coastal areas have been found to contribute to the outbreak of acute infections among tourists, and can be transmitted through contact with polluted recreational water. Salmonella spp. are bacteria frequently associated with waterborne diseases, they can cause various symptoms from mild gastroenteritis to death. This research aimed to determine the concentration of Salmonella in bathing beaches and to evaluate whether the concentrations could be harmful to human health. Samples were collected for the analysis of bacteria and water quality at six different bathing beach sites in Makassar, Indonesia. Salmonella analysis was conducted using a membrane filtration method, where the filter was then placed on Bismuth Sulphite Agar (BSA), a selective medium for Salmonella growth. Salmonella identification was based on a suite of biochemical reaction tests. Salmonella concentration per membrane was determined using a colony counter. Salmonella concentrations were compared between sites using one-way ANOVA with post hoc test, while the correlation between Salmonella concentrations and water quality was evaluated using Principal Component Analysis (PCA). Three colony types grew on the BSA. Salmonella were detected at all six bathing beaches in Makassar. Salmonella concentrations were highest in Tanjung Bayang Beach, followed by Akkarena Beach, Kayangan Island, Lae-lae, Samalona Island, and Bulo Gading Beach. Salmonella concentration correlated with high total organic matter levels, and exceeded the EEC standard for recreational swimming and bathing water at all six bathing beaches in Makassar.